Hard tissue barrier formation in pulpotomized monkey teeth capped with cyanoacrylate or calcium hydroxide for 10 and 60 minutes - Cvek, M.; Granath, L.; Cleaton-Jones, P.; Et al (My University, 1987)
Monkey incisor teeth were pulpotomized in groups of 10. After physiological hemostasis, the pulps of group I were covered with isobutyl cyanoacrylate, and those of groups II and III with calcium hydroxide for 10 and 60 minutes, respectively, whereafter this compound was washed away and the wound surfaces covered with Teflon. In group IV, calcium hydroxide was used as a positive control, and Teflon as a negative control in group V. The animals were killed after 12 weeks and the teeth removed in tissue blocks. The material was processed and evaluated histologically with respect to location and continuity of a hard tissue barrier, type of newly formed hard tissue, state of the pulp, and presence of stainable bacteria in the coronal cavity. Seven of nine teeth in group I showed a hard tissue barrier. The corresponding figure for group II was eight out of 10 teeth. All teeth in groups III and IV had a barrier. The incidence of a continuous barrier increased from group I through group IV, as did the incidence of its location below the level of the original wound surface. The condition of the pulp was related to the presence of bacteria and the continuity of the barrier to the presence of inflammation. There was no bridging in group V. The results support the theory that a low-grade irritation is responsible for the formation of a hard tissue barrier in exposed pulps.
Keywords: Dental Pulp Capping; Cyanoacrylates/therapeutic use; Pulpotomy; Calcium Hydroxide; Cercopithecus aethiops